Using simulated rainfall to evaluate cover crops and winter manure application to limit nutrient loss in runoff. Issue 1 (1st February 2023) - Bhandari, Ammar B.; Gelderman, Ronald; German, David R.; Kharel, Tulsi P.
Abstract: Cover crops can be effective in minimizing nutrient losses from agricultural fields. The objective of this study was to determine the impact of cover crop (rye, Secale cereale L.) and winter manure application on nutrient loss in simulated rainfall runoff. A split block design study with manure (as vertical block) and cover crops (as horizontal block) was established in 2009. Two rain simulations (the first defined as "dry" and the second "wet") using sixteen 4 m 2 steel frames were conducted in May 2010. The runoff volume collected from each plot was analyzed for nitrate–nitrogen (NO3 –N), total suspended solids, total Kjeldahl nitrogen, total phosphorus, and total dissolved phosphorus. In the dry run, the concentration and load of NO3 –N were significantly lower ( p = 0.05) in runoff with the cover crop than in no‐cover crop treatment. Overall, cover crops reduced nutrient loss in concentration by 6%–48% in the dry and 8%–40% in the wet run than with no‐cover crops. The concentration and load of NO3 –N were significantly higher under manure treatments in both "dry" and "wet" runoff runs compared to no‐manure application. Manure application increased nutrient loss in concentration by 6%–58% in the dry and 10%–69% in the wet run than with no‐manure application. This study helps us to understand the complexity of winter manure application with cover crops and potential risks of nutrient loss to surface runoff during spring in the Northern Great plains of the Dakotas. Core Ideas: If winter manure applications are necessary, use fields with cover crops. A cover crop reduced nutrient loss more under manure compared to non‐manured systems. Winter manure incorporation without a cover crop increased nutrient loss in spring runoff.